Gene expression profiles and neural activities of Kenyon cell subtypes in the honeybee brain: identification of novel ‘middle-type’ Kenyon cells - Kaneko, Kumi (Zoological Lett, 2016)
In the honeybee (Apis mellifera L.), it has long been thought that the mushroom bodies, a higher-order center in the insect brain, comprise three distinct subtypes of intrinsic neurons called Kenyon cells. In class-I large-type Kenyon cells and class-I small-type Kenyon cells, the somata are localized at the edges and in the inner core of the mushroom body calyces, respectively. In class-II Kenyon cells, the somata are localized at the outer surface of the mushroom body calyces. The gene expression profiles of the large- and small-type Kenyon cells are distinct, suggesting that each exhibits distinct cellular characteristics. We recently identified a novel gene, mKast (middle-type Kenyon cell-preferential arrestin-related gene-1), which has a distinctive expression pattern in the Kenyon cells. Detailed expression analyses of mKast led to the discovery of novel ‘middle-type’ Kenyon cells characterized by their preferential mKast-expression in the mushroom bodies. The somata of the middle-type Kenyon cells are localized between the large- and small-type Kenyon cells, and the size of the middle-type Kenyon cell somata is intermediate between that of large- and small-type Kenyon cells. Middle-type Kenyon cells appear to differentiate from the large- and/or small-type Kenyon cell lineage(s). Neural activity mapping using an immediate early gene, kakusei, suggests that the small-type and some middle-type Kenyon cells are prominently active in the forager brain, suggesting a potential role in processing information during foraging flight. Our findings indicate that honeybee mushroom bodies in fact comprise four types of Kenyon cells with different molecular and cellular characteristics: the previously known class-I large- and small-type Kenyon cells, class-II Kenyon cells, and the newly identified middle-type Kenyon cells described in this review. As the cellular characteristics of the middle-type Kenyon cells are distinct from those of the large- and small-type Kenyon cells, their careful discrimination will be required in future studies of honeybee Kenyon cell subtypes. In this review, we summarize recent progress in analyzing the gene expression profiles and neural activities of the honeybee Kenyon cell subtypes, and discuss possible roles of each Kenyon cell subtype in the honeybee brain.